18
$\begingroup$

This is Problem 16.17 from the book Exercises in Algebra by A. I. Kostrikin.

Prove that $$ \left|\begin{array}{ccccc} \dfrac{1}{2 !} & \dfrac{1}{3 !} & \dfrac{1}{4 !} & \cdots & \dfrac{1}{(2 k+2) !} \\ 1 & \dfrac{1}{2 !} & \dfrac{1}{3 !} & \cdots & \dfrac{1}{(2 k+1) !} \\ 0 & 1 & \dfrac{1}{2 !} & \cdots & \dfrac{1}{(2 k) !} \\ \vdots & \vdots & \vdots & \ddots & \vdots \\ 0 & 0 & 0 & \cdots & \dfrac{1}{2 !} \end{array}\right|=0, \quad k \in \mathbb{N} $$

My Attempt: I tried to expand it by the first column, but it seemed to be more complicated when I did that. I also tried to add edges to the determinant(in the hope that it will be easier to calculate), but I still failed to work it out.

So, My Question is, how to calculate this determinant?

$\endgroup$
4
  • 1
    $\begingroup$ My first thought would be to reduce it to triangular form. I would take a reasonable size example, say $k=3$ and keep track of the factors I use to do the reduction. Then look for a pattern and try to prove it works. $\endgroup$
    – saulspatz
    Dec 3 '20 at 16:11
  • $\begingroup$ The hint in math.stackexchange.com/a/3288338 gives the recursive formula $d_0 = 1, d_1 = \frac12, d_2 = \sum_{k=0}^n \frac {(-1)^{k+1}}{(k+1)!} d_{n-k}$ for when the determinant is of size $k \times k$. This method probably wouldn't work (considering the fact that the determinant do not vanish for even $k$), and even if it does, it will be terribly unsatisfying. $\endgroup$
    – player3236
    Dec 3 '20 at 16:39
  • 3
    $\begingroup$ There's definitely a pattern in the nullspace. For $k = 1,2,3,4$ we have the following solutions to $Mx = 0$. $$ (1,-6,12)\\ (1,0,-6,36,-72)\\ (1,0,-42,0,2520,-15120,30240)\\ (1,0,-4,0,1680,0,-100800,604800,-1209600) $$ $\endgroup$ Dec 4 '20 at 0:48
  • $\begingroup$ I tried something with the explicit formula which was interesting, although useless. The relevant permutations satisfy σ(i) ≥ i-1, which is enough to show that σ decomposes into disjoint shift-left-cycles, e.g. (5432). Counting 1-cycles, this corresponds to a partition of $\{1, \ldots, n-1\}$ into consecutive blocks. If these have lengths $j_1, \ldots, j_k$, resp., the contributed summand should be $(-1)^{n-1 + k}\prod_{i=1}^k 1/(j_i+1)!$. Summing over all $k$ and all such multiindices $J$, this gives the det, but I failed to see anything like e.g. a useful $\pm$-pairing. $\endgroup$ Dec 4 '20 at 7:28
7
$\begingroup$

We want to prove that the $(n-1)\times(n-1)$ matrix $$ A_n=\pmatrix{ \dfrac{1}{2!} &\dfrac{1}{3!} & \cdots &\cdots & \cdots &\dfrac{1}{n!} \\ 1 &\dfrac{1}{2!} &\dfrac{1}{3!} &\cdots &\cdots &\dfrac{1}{(n-1)!} \\ 0 & 1 & \ddots & \ddots & \ddots & \vdots\\ \vdots & \ddots & \ddots & \ddots&\ddots & \vdots\\ \vdots & \ddots & \ddots &1& \dfrac{1}{2!} & \dfrac{1}{3!}\\ 0 & \cdots & \cdots & 0 & 1 & \dfrac{1}{2!} } $$ is singular when $n\ge4$ is even. This can be proved by mathematical induction on $n$. The base case $n=4$ can be verified directly. In the inductive step, note that for any positive integer $m$, $$ \sum_{k=0}^m\frac{(-1)^k}{k!}\frac{1}{(m-k)!}=\frac{1}{m!}\sum_{k=0}^m(-1)^k\binom{m}{k}=\frac{1}{m!}(1-1)^m=0. $$ Move the first and the last summands out of the sum, we obtain $$ \frac{1}{m!}+\sum_{k=1}^{m-1}\frac{(-1)^k}{k!}\frac{1}{(m-k)!}=\frac{(-1)^{m+1}}{m!}. $$ Denote the $i$-th row of $A_n$ by $a_i$. The previous identity means that \begin{aligned} u&:=a_1+\sum_{k=1}^{n-1}\frac{(-1)^k}{k!}a_{k+1}\\ &=\left(-\frac{1}{2!},\,\frac{1}{3!},\,-\frac{1}{4!},\,\frac{1}{5!},\,\ldots,\,-\frac{1}{(n-2)!},\,\frac{1}{(n-1)!},\,\frac{1}{(n-1)!}-\frac{1}{n!}\right). \end{aligned} (Note that the last entry of $u$ is not $-\frac{1}{n!}$, because the last column of $A_n$ ends with $\frac{1}{2!}$, not $1$.) In other words, by some appropriate elementary row operations, we can modify the first row of $A$ to $u$. Therefore, by the multilinearity of the determinant function, $\det(A_n)$ remains unchanged if we replace the first row of $A_n$ by $$ v:=\frac12(a_1+u) =\left(0,\,\frac{1}{3!},\,0,\,\frac{1}{5!},\,\ldots,\,0,\,\frac{1}{(n-1)!},\,\frac{1}{2\times(n-1)!}\right). $$ Now suppose $n\ge6$ is even. By Laplace expansion along $v$ and by induction assumption, we get \begin{aligned} \det(A_n) &=-\frac{1}{3!}\det(A_{n-2})-\frac{1}{5!}\det(A_{n-4})-\cdots-\frac{1}{(n-1)!}\det(A_2)+\frac{1}{2\times(n-1)!}\\ &=-\frac{1}{(n-1)!}\det(A_2)+\frac{1}{2\times(n-1)!}\\ &=-\frac{1}{(n-1)!}\frac{1}{2!}+\frac{1}{2\times(n-1)!}\\ &=0. \end{aligned}

$\endgroup$
7
$\begingroup$

Finally I found a direct way to work this out, that is, to use Generating Functions.


From this article we get the following proposition:

Proposition. Consider the following infinite matrix with $1$s in the super diagonal. $$ D=\left[\begin{array}{ccccc} b_{0} & 1 & 0 & 0 & \cdot \\ b_{1} & c_{1} & 1 & 0 & . \\ b_{2} & c_{2} & c_{1} & 1 & . \\ b_{3} & c_{3} & c_{2} & c_{1} & . \\ b_{4} & c_{4} & c_{3} & c_{2} & . \\ \cdot & . & . & . & . \end{array}\right] $$ Let $B(x)=\sum_{n=0}^{\infty} b_{n} x^{n},$ and $C(x)=\sum_{n=1}^{\infty} c_{n} x^{n}$ be the generating functions for the sequences $b_{0}, b_{1}, b_{2}, \ldots$ and $c_{1}, c_{2}, c_{3}, \ldots,$ respectively. If $$ A(x)=\frac{B(x)}{1+C(x)}=\sum_{n=0}^{\infty} a_{n+1} x^{n} $$ then $a_{n}=(-1)^{n-1} D_{n}$ and $1+x A(-x)$ is the generating function of $D_{n}$.

For the original problem, it is equivalent to calculate the determinant: $$ D=\left| \begin{matrix} \dfrac{1}{2!}& 1& 0& \cdots& 0\\ \dfrac{1}{3!}& \dfrac{1}{2!}& 1& \cdots& 0\\ \dfrac{1}{4!}& \dfrac{1}{3!}& \dfrac{1}{2!}& \cdots& 0\\ \vdots& \vdots& \vdots& \ddots& \vdots\\ \dfrac{1}{\left( 2k+2 \right) !}& \dfrac{1}{\left( 2k+1 \right) !}& \dfrac{1}{\left( 2k \right) !}& \cdots& \dfrac{1}{2!}\\ \end{matrix} \right| $$

We can see that $\displaystyle B(x)=\sum _{i=0}^{\infty } \frac{x^{i}}{(i+2)!}= \frac{-x+e^x-1}{x^2}$, $\displaystyle C(x)=\sum _{i=1}^{\infty } \frac{x^i}{(i+1)!} = \frac{-x+e^x-1}{x}$, so $A(x)=\dfrac{1}{x}+\dfrac{1}{1-e^x}$, and finally the generating function for $D_n$ is $D(x)=\dfrac{x}{e^x-1}+x$.

Notice the order $N$ of original matrix $D$ is always odd (since $N=(2k+2)-2+1=2k+3$), so the original claim is equivalent to when $n>4$ and $n$ is odd, $[x^n]D(x)=0$. It's easy to see that $D(x) -1 - x/2$ is an even function, which implies its series only contains terms of the form $x^{2k}$, thus we finished our proof.


I think this method really requires a good understanding of linear equations and Cramer's Law, along with the knowledge of generating functions.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.